2017
DOI: 10.1128/aem.03151-16
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Salmonella enterica in Meat in Less than 5 Hours by a Low-Cost and Noncomplex Sample Preparation Method

Abstract: Salmonella is recognized as one of the most important foodborne bacteria and has wide health and socioeconomic impacts worldwide. Fresh pork meat is one of the main sources of Salmonella, and efficient and fast methods for detection are therefore necessary. Current methods for Salmonella detection in fresh meat usually include Ͼ16 h of culture enrichment, in a few cases Ͻ12 h, thus requiring at least two working shifts. Here, we report a rapid (Ͻ5 h) and high-throughput method for screening of Salmonella in sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 36 publications
2
15
0
1
Order By: Relevance
“…Actually, the plate counts indicated that 2 cfu/25 g could be reliably detected. This result compares favorably with other molecular biology‐based methods previously published for this and/or other bacterial pathogens (Fachmann et al., ; Garrido‐Maestu et al., ; Garrido‐Maestu, Fuciños, Azinheiro, Carvalho, & Prado, ). The RLOD was determined to be 1.6, with a z‐Test of 0.975 (<2).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Actually, the plate counts indicated that 2 cfu/25 g could be reliably detected. This result compares favorably with other molecular biology‐based methods previously published for this and/or other bacterial pathogens (Fachmann et al., ; Garrido‐Maestu et al., ; Garrido‐Maestu, Fuciños, Azinheiro, Carvalho, & Prado, ). The RLOD was determined to be 1.6, with a z‐Test of 0.975 (<2).…”
Section: Discussionsupporting
confidence: 81%
“…FP: positive by the alternative method not confirmed as such while the reference method obtained a negative result). The reclassification of the deviations was performed as described previously (Fachmann et al., ; NordVaL, ).…”
Section: Methodsmentioning
confidence: 99%
“…; Fachmann et al . ). In the present study, we demonstrated that a 6‐h enrichment was necessary for one‐step RT‐qPCR assay to improve the recovery and detection of low inocula levels (< 10 2 CFU per g) of Salmonella cells in most fresh‐cut vegetable samples.…”
Section: Resultsmentioning
confidence: 97%
“…Pork meat is the main product among worldwide meat production (Sánchez‐Ortega et al, ). Pork remains an important source of human foodborne pathogen (Fachmann et al, ). Antibacterial substances are added to food to ensure its safety and extend its shelf life (Suo et al, ).…”
Section: Introductionmentioning
confidence: 99%